A case for integrity: gains from including more than animal welfare in animal ethics committee deliberations. (January 2014) - Röcklinsberg, H; Gamborg, C; Gjerris, M
From January 2013, a new EU Directive 63/2010/EU requires that research using animals must undergo a harm–benefit analysis, which takes ethical considerations into account (Art. 38 (2) d) – a so-called 'project authorization' (Art. 36). A competent authority in each member state has to ensure that no project is carried out without such a project validation process, but often delegates the actual assessment to an animal ethics committee (AEC) or its equivalent. The core task of the AEC is to formulate a justifiable balance between the animals' suffering caused by research and the potential human benefit. AECs traditionally focus on animal welfare issues, but according to the new directive other public concerns must also be taken into account. Taking the new EU Directive as a point of departure, the central aim of this paper is to discuss the evaluation process in relation to animal welfare and animal ethics through the concept of animal integrity. A further aim is to elaborate on possible improvements to project evaluation by considering animal integrity. We argue that concepts like animal integrity are often left out of project authorization processes within AECs, because animal ethics is often interpreted narrowly to include only certain aspects of animal welfare . Firstly, we describe the task of an AEC and discuss what has typically been regarded as ethically relevant in the assessment process. Secondly, we categorize four notions of integrity found in the literature to show the complexity of the concept and furthermore to indicate its strengths. Thirdly, we discuss how certain interpretations of integrity can be included in AEC assessments to encapsulate wider ethical concerns and, perhaps even increase the democratic legitimacy of AECs.